(untitled) (Politeja, 2015)
The Book of Esther and Shoah: Biblical, Exciting and Attractive Face of Postmemory The article contains an analysis of the construction of the narrative of the Shoah, using motifs from the Book of Esther. Non‑fiction book: Code of Esther, 2013 (Le Code d’Esther, 2012), written by French journalists: Bernard Benyamin and Yohan Perez is a record of investigative journalism. During the investigation various interpretations of the “enigmatic” words of Julius Streicher – a Nazi war criminal in the context of the biblical text are recalled. The title of the book and its cover’s design predicts sensation while the attractiveness of the communication is achieved by using of multimedia elements (online videos illustrating the described events, accessible through QR codes placed in the book), and an invitation to interact through thematic websites, social networking sites like Facebook and Twitter. The authors, belonging to the “second generation”, derive knowledge and experiences through mediation, which is the reason of the treatment of the book in terms of post‑memory.